ANALISIS BENDING SHAFT PROPELLER PADAKAPAL DENGAN VARIASI BEBAN MENGGUNAKANMETODE FEM - Arya Adhikara Idris (2022)
In the shipping system, one of them is the ship propulsion system in which there is a propulsion system to move the ship produced from the main engine. With this main engine as the main driving motor, the ship can sail at sea, from the combustion results to the energy that is channeled to the propeller through the gearbox and delivered by the propeller shaft. in a work process there must be a failure of work or human error in installing a workpiece. One of them is on the propeller shaft. There are some work failures that occur such as misalignment, bending and fractures that occur in the shaft. This study was carried out to calculate and predict the occurrence of bending in the shaft. This research uses the FEM method which is assisted by the ansys 2021 R2 software to be simulated and find the point or area of the bending with load variations using calculations of speed, thrust force and torque moments that affect the performance of the shaft propeller. This shaft uses 316 stainless steel material with a length of 6.77 meters and has a diameter of 0.16 meters. With structural ansys software, it facilitates this research by obtaining a minimum bending value that occurs at a speed of 7 knots with a thrust force of 43.20 kN and an area of 0.12262 occurring at the end of the shaft propeller. For the maximum bending value occurs at a speed of 12 knots with a thrust force of 133.30 kN and an area of 3.4027 occurs at the end of the shaft propeller. from the obtained value that the average bending increase value is 2,11/knot. By using a 2 x 1200 Hp engine with 850 rpm, the engine can only deliver a maximum of 840 rpm because the maximum speed limit is at 12knots Keywords : Shaft propeller, Bending shaft, Engine vibration